2016
DOI: 10.1016/j.fertnstert.2016.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Growth trend of small uterine fibroids and human chorionic gonadotropin serum levels in early pregnancy: an observational study

Abstract: A remarkable nonlinear growth of small fibroids during initial pregnancy was observed, with a faster rate in the first trimester and a slowdown by midpregnancy. Those changes seem to be related to the similar increase of hCG levels until 12 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 17 publications
1
39
0
Order By: Relevance
“…There are poor data in the literature on the recommendation for elective preconception myomectomy in asymptomatic women with fibroids . Preconception myomectomy seems to reduce uterine contractility, restore normal anatomy and stop local inflammation . In contrast, it may provoke endometrial damage and pelvic adhesions, responsible for unfavorable obstetric outcomes.…”
Section: Impact Of Myomas On Infertility (Effectiveness Of Myomectomy)mentioning
confidence: 99%
“…There are poor data in the literature on the recommendation for elective preconception myomectomy in asymptomatic women with fibroids . Preconception myomectomy seems to reduce uterine contractility, restore normal anatomy and stop local inflammation . In contrast, it may provoke endometrial damage and pelvic adhesions, responsible for unfavorable obstetric outcomes.…”
Section: Impact Of Myomas On Infertility (Effectiveness Of Myomectomy)mentioning
confidence: 99%
“…As alluded above, several reports have been published with the aim to clarify the influence of pregnancy on uterine leiomyomas but conclusions are not fully consistent [ 13 , 16 , 17 , 19 , 20 , 21 , 22 , 23 ]. The controversies among studies investigating the effects of pregnancy on fibroid growth can be explained by differences in the study design, the population studied and timing of ultrasound evaluations [ 13 , 16 , 17 , 19 , 20 , 21 , 22 , 23 ]. Noteworthy, some contributions have assessed leiomyoma increase during pregnancy starting after the 10th week of pregnancy and thus quite late to monitor correctly the growth pattern.…”
Section: Pattern Of Growth Of Uterine Leiomyomas During Pregnancymentioning
confidence: 99%
“…The logistic regression analysis revealed that the volumetric change occurred mainly in the first half of pregnancy and was influenced negatively by parity and positively by pre-pregnancy BMI, while maternal age correlated negatively with leiomyoma growth over the entire course of pregnancy [ 13 ]. Ciavattini et al examined 109 pregnant women who underwent an ultrasound scan before pregnancy, a second one at 7–8 weeks of gestation, a third examination at 10–13 week of gestation and a fourth scan at 20–22 weeks of gestation [ 19 ]. A significant increase for most leiomyomas during the first half of pregnancy (a median growth rate of 122% during the interval between the first and the second scan; median growth rate of 108% between the second and third ultrasound; median growth rate of 25% between the third and fourth ultrasound) without a linear correlation between the growth trend and the gestational age (small leiomyomas seemed to grow at a faster rate in the first trimester and to undergo a slow down by mid-pregnancy) was reported.…”
Section: Pattern Of Growth Of Uterine Leiomyomas During Pregnancymentioning
confidence: 99%
See 2 more Smart Citations